Análise de imagem dos cartazes do festival de cinema de Cannes de 1970 a 1979 - Coca, Guilherme Alencar (2019)
This work aims to understand and analyze the posters of the Cannes Film Festival and its importance for the cinema and as a design work. The work was elaborated in three stages, in the first one is exposed the history of Cannes Festival; in the second it was tried to understand the media poster as a whole and how it was used by the cinema; and in the third stage the image analysis of the posters of Cannes Festival from the decades of 1970 to 1979 were made. The image analysis was made from the semiotic method of the author Martine Joly, elaborating a table, and from this, was elaborated syntheses that were used in the study texts. The work showed how the publicity posters use certain design strategies, and also how these posters talk to other posters of their day.